To solve the inequality \((x - 9)^3 < 64\), we first rewrite the inequality in a more manageable form:
-
Identify when \((x - 9)^3 = 64\).
Taking the cube root of both sides, we have: \[ x - 9 = \sqrt[3]{64} \] Since \(\sqrt[3]{64} = 4\), we can add 9 to both sides to solve for x: \[ x - 9 = 4 \implies x = 4 + 9 = 13 \]
-
Next, we analyze the inequality \((x - 9)^3 < 64\): The inequality implies: \[ (x - 9)^3 < (4)^3 \] Which gives us: \[ (x - 9) < 4 \quad \text{or} \quad (x - 9) > -4 \]
-
Solve the first inequality: \[ x - 9 < 4 \implies x < 13 \]
-
Solve the second inequality: \[ x - 9 > -4 \implies x > 5 \]
-
Combine the results: The solution for \((x - 9)^3 < 64\) is: \[ 5 < x < 13 \]
In interval notation, this solution is expressed as: \[ (5, 13) \]
Thus, the correct choice is: B. The solutions are the values of x in the interval (5, 13).